NEW MECHANISMS FOR THE POWER SWITCHER WITH V EXTINGUISHING CHAMBERS - OVIDIU ANTONESCU; NATAȘA NEDELA; PĂUN ANTONESCU (Journal of Engineering Studies and Research)
Starting from an existing V power switcher mechanism, the paper presents two new kinematic schemes of the V switcher mechanisms for medium and high power. The proposed schemes consist of triadic chains that ensure transmission angles near to the optimum values. The geometric and kinematic analyses of the proposed mechanisms, with\ driven components that have to move with high speeds on disengaging process in the extinguishing chamber, have been achieved. In the second section of the paper, an optimum kinematic scheme of the V power switcher with triadic chain type 4R+2T has been presented.